(untitled) (Economics and region, 2017)
UDC 368 Viktor Smoliak, PhD, Associate Professor. Kharkiv National Simon Kuznets University of Economics. European vector of development of the insurance companies investment activity. The article investigates Ukrainian insurance market problems and peculiarities of the insurance companies investment activity. The author defined the differences between Ukrainian insurance companies investment activity and European insurance companies investment activity. There are justified the main directions of development of Ukrainian insurance market in the article. Keywords: insurance, insurance company, investment activity, insurance market, development of insurance.